Patient-derived colorectal microtumors predict response to anti-PD-1 therapy - Nguyen, Duy T.; Schaller, Matthew A.; Terracina, Krista P.; Xu, Xia; Pedro, Diego I.; Pepe, Alfonso; Urueña, Juan M.; Dupee, Zadia; Diodati, Nickolas; Smolchek, Ryan A.; Famiglietti, Jack E.; Nguyen, Nhi Tran Yen; et al. (Frontiers in Immunology, 2025)
Immune checkpoint inhibitors have made remarkable impacts in treating various cancers, including colorectal cancer (CRC). However, CRC still remains a leading cause of cancer-related deaths. While microsatellite instability (MSI) CRC has shown positive responses to anti-PD-1 therapy, this subgroup represents a minority of all CRC patients. Extensive research has focused on identifying predictive biomarkers to understand treatment response in CRC. Interestingly, a growing number of clinical cases have reported favorable outcomes from a subtype of supposedly non-responder microsatellite stable (MSS) CRC, characterized by DNA polymerase ϵ (POLE) proofreading domain mutations with high tumor mutational burden (TMB). This subtype has shown a notable response, either partial or complete, to pembrolizumab as salvage treatment, often following significant disease progression. To improve efficiency, cost-effectiveness, and clinical outcomes, there is an essential need for a testing platform capable of promptly identifying evidence of anti-PD-1 response to inform treatment strategies. Here, we established a novel 3D ex vivo immunotherapy model using patient-derived tumor microexplants (or microtumors <1 mm) co-cultured with autologous peripheral blood mononuclear cells (PBMCs) from treatment-naïve CRC patients. We demonstrate that long-term ex vivo treatment with pembrolizumab induced a heterogeneous but appreciable interferon-gamma (IFN-γ) secretion, accompanied by infiltrating PBMCs. Intriguingly, a case study involving an MSS CRC phenotype harboring POLE mutation and associated ultrahigh TMB demonstrated a response to PD-1 blockade, potentially from the intratumoral immune cell population. Ultimately, this novel model could serve as a valuable tool in complementing clinical diagnostics and guiding personalized treatment plans for CRC patients, particularly those with specific phenotypes and mutational profiles.